2018
DOI: 10.1101/389940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary prediction of the potential distribution and consequences of Haemaphysalis longicornis using a simple rule-based climate envelope model

Abstract: Haemaphysalis longicornis, the Asian longhorned (or bush) tick has been detected on a sheep in August 2017 in Hunterdon County, New Jersey. By September 8, 2018, this tick has been detected in 31 counties in 9 states along the Atlantic coast of the United States, with the first detection backdated to 2010. Here, I use a simple rule-based climate envelope model, based on a prior analysis in New Zealand, to provide a preliminary analysis of the potential range of this introduced tick species in North America. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Currently, all published models of H. longicornis distribution use climatic variables to predict distribution [27][28][29]45]. Ecological zones have also been included as these can represent a complex of interacting abiotic and biotic variables [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, all published models of H. longicornis distribution use climatic variables to predict distribution [27][28][29]45]. Ecological zones have also been included as these can represent a complex of interacting abiotic and biotic variables [28].…”
Section: Discussionmentioning
confidence: 99%
“…The parthenogenetic populations are distributed in Australia, New Zealand, New Caledonia, Fiji, New Hebrides, Tonga, northeastern Russia, northern Japan, Kyushu and Yakushima in southern Japan, and Sichuan and Shanghai in China [1,25,26]. Modeling has indicated areas along the Gulf and Atlantic coast of eastern North America as the potential geographical range of H. longicornis expansion [27]. Other modeling studies have indicated the potential expansion and distribution of this tick species in eastern North America from southern Canada to the Gulf coast, and in a small temperate area on the west coast [28], and the southeastern United States, the Pacific Northwest, and central and southern Mexico [29].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, recent evidence supports the establishment of the Asian Longhorned tick ( Haemaphysalis longicornis ) in the USA by an undefined origin of introduction [ 35 , 36 ]. There is no clear impact data of this tick to the USA economy; however, its introduction into New Zealand and Australia has resulted in high economic losses to their cattle industries [ 35 , 37 ]. Similarly, if A. variegatum or other Amblyomma species native to Africa were to be introduced along with E. ruminantium into the USA, then heartwater could spread rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…To aid in the understanding and management of the exotic H. longicornis, extensive work has been conducted on the natural history and spread of this tick within the United States (16,17,22,(30)(31)(32). These studies largely rely on the quick and accurate identification of H. longicornis using key morphological features found on the mouth parts (1).…”
Section: Introductionmentioning
confidence: 99%